Through our eyes: teachers using cameras to engage in environmental education curriculum development processes - du Toit, Derick (Rhodes University, Faculty of Education, Department of Education, 1999)
This research explores the potential for engaging teachers in school-based environmental education curriculum development processes by using camera. The research, through its epistemological and ontological position, is closely linked to educational orientations associated with aspects of outcomes-based educational transformation in South Africa. A participatory approach that recognises teachers as co-researchers, each bringing to the inquiry her or his questions and constructions of meaning, was adopted. Participatory inquiry was initiated by setting up cluster meetings that allowed for teacher inputs through open dialogic processes. Fundamental to the inquiry is the notion that context shapes curriculum and curriculum development processes. It was from this orientation that a group of 13 teachers, using cameras to create visual narratives, explored their own diverse and complex contexts. These narratives (or stories) form the basis for further inquiry and development of sophistication with respect to the concept of environment. The research process is critically and reflexively documented as a series of field and research texts constructed from a variety of data sources gathered over the period of one year. The work is presented as a process of engaging critically with environmental education curriculum development and an opportunity to raise questions, rather than seek answers in this regard.
Keywords: Environmental education -- South Africa; Curriculum change -- South Africa; Photography in education; Competency-based education -- South Africa